Parental Involvement in Mathematics Achievement and Motivation: Male vs Female Students - Sumantri, Astri Wiliastri; Sri Subanti; Budi Usodo; Getut Pramesti (Journal of Education Technology, 2025)
This study seeks to evaluate how these two independent variables, both individually and interactively, influence students’ academic outcomes. This study aims to analyze the interaction between parental involvement and gender in shaping students’ mathematics achievement and learning motivation at the junior secondary level. A 2×2 factorial non-experimental design was employed involving 261 Indonesian middle school students, which was selected via proportional stratified sampling. Data were collected using three instruments: the Student-Rated Parental School Involvement Questionnaire, the Mathematics Motivation Questionnaire, and students’ midterm exam scores. The dataset was analyzed using MANOVA. The results revealed three key findings. First, a significant interaction effect was found between gender and parental involvement on mathematics achievement (F = 5.476; Sig. = 0.020), with boys receiving partial support performing the lowest. Second, gender had a significant main effect (F = 7.644; Sig. = 0.006), with girls outperforming boys. Third, parental involvement significantly improved students’ motivation (F = 27.037; Sig. = 0.000). These findings highlight the importance of responsive family engagement and suggest the need for gender-sensitive collaboration between families and schools to foster equitable and sustained learning in mathematics.